2019
DOI: 10.2147/ott.s189001
|View full text |Cite
|
Sign up to set email alerts
|

<p>TRIB3 suppresses proliferation and invasion and promotes apoptosis of endometrial cancer cells by regulating the AKT signaling pathway</p>

Abstract: Objective The aim of this study was to examine the effect of TRIB3 on proliferation, apoptosis, and migration of endometrial cancer (EC) cells and explore the relationship between TRIB3 and AKT signaling pathway in EC progression. Methods Immunohistochemical analysis was performed to measure the expression level of TRIB3 in normal endometrium tissues and EC tissues. Overexpression and shRNA knockdown techniques were applied by transfecting EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Endometrial carcinoma is one of the most frequently diagnosed gynaecological malignancies, characterized by high rates of recurrence and poor prognosis. 22 Neddylation, a post-translational modification that conjugates the ubiquitin-like protein NEDD8 to substrate proteins, is an important biochemical process that regulates protein function. 20 The neddylation pathway is reported to be overactivated in multiple cancer types, including liver, lung and colon cancer, and its overactivation indicates poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial carcinoma is one of the most frequently diagnosed gynaecological malignancies, characterized by high rates of recurrence and poor prognosis. 22 Neddylation, a post-translational modification that conjugates the ubiquitin-like protein NEDD8 to substrate proteins, is an important biochemical process that regulates protein function. 20 The neddylation pathway is reported to be overactivated in multiple cancer types, including liver, lung and colon cancer, and its overactivation indicates poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Felip et al [ 12 ] found that ABTL0812 (an anti-cancer drug) inhibited the PI3K/AKT/mTORC1 axis by up-regulating the expression of TRIB3 to sensitize endometrial cancer cells. Qu et al [ 13 ] found that the expression level of TRIB3 in endometrial cancer cells was higher than that in normal endometrial tissue. The overexpression of TRIB3 promoted endometrial cell apoptosis, while it inhibited cell proliferation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…TRIB3 mediates differential regulation of the degree of Akt phosphorylation in different cells. In endometrial cancer cells, TRIB3 enhanced cell apoptosis and suppressed cell proliferation and migration ability through inhibition of Akt [14]. However, TRIB3 promoted oral squamous cell carcinoma cell proliferation by increasing Akt phosphorylation [31].…”
Section: Discussionmentioning
confidence: 97%
“…Yan reported that palmitic acid (PA), an important FFA constituent in GCs can induce endoplasmic reticulum stress (ERs) in a human hepatic cell line, accompanied by a signi cant induction of tribbles of pseudokinase 3 (TRIB3) expression, which was associated with decreased levels of phosphorylated Akt (p-Akt) [12]. Moreover, some other reports showed that TRIB3 induces abnormal Akt phosphorylation under high PA conditions in various cells [13][14][15]. On the other hand, TRIB3 was involved in cell proliferation and fatty acid oxidation signaling in bovine cumulus cells, which are also derived from follicular cells as granulosa cells and played a key role in oocyte meiotic resumption regulation [16].…”
Section: Introductionmentioning
confidence: 99%